The fibularis tertius muscle revisited: comparative anatomy, developmental classification, and evolutionary-clinical implications - Olewnik, Łukasz; Landfald, Ingrid C.; Domosławka, Daria; Triantafyllou, George; Georgiev, Georgi P.; Piagkou, Maria (Frontiers in Cell and Developmental Biology, 2025)
The fibularis tertius muscle (FTM) has long been regarded as an accessory or vestigial structure with inconsistent presence in the human population. However, recent anatomical, developmental, and biomechanical evidence suggests that FT is a functional and evolutionarily novel muscle with distinct clinical implications. This review synthesizes current knowledge on FT morphology, embryological development, phylogenetic context, imaging challenges, and surgical relevance. A unified classification of its proximal and distal attachments is proposed for both fetal and adult populations. The clinical significance of FT variants, including agenesis and fusion with adjacent structures, is examined in the context of tendon harvesting, lateral ankle stabilization, and nerve assessment. Additionally, future directions are outlined, including fetal imaging, biomechanical modeling, and comparative EMG studies, aiming to integrate FT more comprehensively into anatomical atlases, radiological protocols, and surgical planning.